2018
DOI: 10.1159/000489381
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Keratin 9 Missense Mutation in a Chinese Family with Epidermolytic Palmoplantar Keratoderma

Abstract: Background/Aims: Epidermolytic palmoplantar keratoderma (EPPK) is an autosomal dominant genodermatosis. It is characterized by diffuse yellow keratoses on the palmoplantar epidermis, with an erythematous border. The keratin 9 gene (KRT9) and less frequently the keratin 1 gene (KRT1) are responsible for EPPK. This study aims to identify and analyse genetic defects responsible for EPPK in a Han Chinese pedigree. Methods: A four-generation Han Chinese pedigree containing five individuals affected with EPPK was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Researchers at home and abroad have found that the 163rd amino acid is the hotspot mutation region of the KRT9 gene (48 of 100 cases) (Rugg et al, 2002). EPPK combined with knuckle pads maybe associated with mutations in many KRT9 genes, such as p.Met157Thr, p.Leu160Phe, p.Asn161Ser,p.Arg163Trp, p.Leu168Ser, p.Cys406Arg, and p.Leu458Pro (Escobar et al, 2007; Codispoti et al, 2009; Li et al, 2009; Wang et al, 2010; Du et al, 2011; Mao et al, 2018; Xiao et al, 2018). In this study, we studied three large Chinese families with EPPK and found 3 heterozygous gene mutations of KRT9: c.482A>G (p.Asn161Ser), c.487C>T (p.Arg163Trp) and c.488G>A (p.Arg163Gln).These mutations were not found in normal members of three families and in 100 healthy controls, indicating that the mutations detected in the families were the pathogenic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers at home and abroad have found that the 163rd amino acid is the hotspot mutation region of the KRT9 gene (48 of 100 cases) (Rugg et al, 2002). EPPK combined with knuckle pads maybe associated with mutations in many KRT9 genes, such as p.Met157Thr, p.Leu160Phe, p.Asn161Ser,p.Arg163Trp, p.Leu168Ser, p.Cys406Arg, and p.Leu458Pro (Escobar et al, 2007; Codispoti et al, 2009; Li et al, 2009; Wang et al, 2010; Du et al, 2011; Mao et al, 2018; Xiao et al, 2018). In this study, we studied three large Chinese families with EPPK and found 3 heterozygous gene mutations of KRT9: c.482A>G (p.Asn161Ser), c.487C>T (p.Arg163Trp) and c.488G>A (p.Arg163Gln).These mutations were not found in normal members of three families and in 100 healthy controls, indicating that the mutations detected in the families were the pathogenic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Sanger sequencing was also performed on 200 control subjects to confirm the frequency of the identified variant in the cohort from central south China. Primers that were used for PCR amplification were designed and confirmed by Primer3 program and Primer-Basic Local Alignment Search Tool [25,26]. The sequences of the primers were 5 -CTCCTCAGGACCAGGCTTC-3 and 5 -TGACCCTCTGTACCCTCTGG-3 .…”
Section: Variant Analysismentioning
confidence: 99%
“…Palmoplantar keratoderma (PPK) is a group of heterogenous genodermatoses characterized by hyperkeratotic skin in the palms and soles, clinically grouped into four patterns: diffuse, striate, focal, and punctate (Fukunaga, Kubo, Sasaki, Tsuruta, & Fukai, ; Knöbel, O'Toole, & Smith, ; Mao, Zhang, You, Xiao, & Zhao, ; Smith et al, ; Wang et al, ; Xiao et al, ). Epidermolytic palmoplantar keratoderma (EPPK, OMIM144200) is a rare skin disorder with the main clinical feature of diffuse hyperkeratotic skin in the palms and soles (Wang et al, ; Xiao et al, ). Generally, no subjective symptoms accompany the disorder except mild itching.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of this wide group of disorders involves structural proteins (keratins), cornified envelope (loricrin, transglutaminase), cohesion (plakophilin, desmoplakin, desmoglein1), cell‐to‐cell communication (connexins), and transmembrane signal transduction (cathepsin C) proteins (Chen et al, ; Li, Han, Han, Zeng, Zhang, & Ma, ; Li, Wen, et al, ). An autosomal dominant inheritance is usually seen in EPPK (Fukunaga et al, ; Knöbel et al, ; Mao et al, ; Smith et al, ; Wang et al, ; Xiao et al, ). The genetic basis of EPPK has also been explored.…”
Section: Introductionmentioning
confidence: 99%